2006
DOI: 10.1110/ps.051906706
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phosphorylation sites in glycine N‐methyltransferase from rat liver

Abstract: Previous studies have shown that rat glycine N-methyltransferase (GNMT) is phosphorylated in vivo, and could be phosphorylated in vitro on serine residues with a significant increase of enzyme activity, but no phosphorylation sites were identified. In this work the identification of the specific phosphorylation sites of rat GNMT is reported. Three different preparations of rat GNMT were analyzed: (1) purified from liver by standard methods of protein purification, (2) prepared from isolated hepatocytes and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…Purity of the final protein samples was at least 98% as determined by scanning of the gel after SDS electrophoresis and Coomassie staining. As reported previously, the N-terminal residue in liver GNMT was acetylated valine but in recombinant protein the N-terminal valine was not acetylated [23,25].…”
Section: Protein Preparationsupporting
confidence: 74%
See 2 more Smart Citations
“…Purity of the final protein samples was at least 98% as determined by scanning of the gel after SDS electrophoresis and Coomassie staining. As reported previously, the N-terminal residue in liver GNMT was acetylated valine but in recombinant protein the N-terminal valine was not acetylated [23,25].…”
Section: Protein Preparationsupporting
confidence: 74%
“…In an earlier study we showed that both purified native liver and recombinant GNMT proteins contain small amounts of phosphorylated serine residues [25]. Only a single species with a mass corresponding to the N-terminal acetylated form was found by LC-MS/MS analysis of the native liver enzyme.…”
Section: Protein Preparationmentioning
confidence: 96%
See 1 more Smart Citation
“…The initial methionine residue is removed, and GNMT proteins from liver or expressed in E. coli have an N-terminal valine. The N-terminal valines in rat and human GNMTs are acetylated, but when recombinant rat or human GNMT is expressed in E. coli, they are not acetylated (16,17). The only known posttranslational modification of liver GNMT is serine phosphorylation.…”
Section: Gnmt Genes and Proteinsmentioning
confidence: 99%
“…The only known posttranslational modification of liver GNMT is serine phosphorylation. Serines 9, 71, 139, 182, and 241 may be partially phosphorylated in rat liver and recombinant GNMTs, but in the purified rat liver enzyme, the amount of phosphorylation is very low (17). Ser 9 of rat GNMT can be phosphorylated in vitro by the glucagon-activated cAMP-dependent protein kinase (18).…”
Section: Gnmt Genes and Proteinsmentioning
confidence: 99%